2011
DOI: 10.1177/0013916511402673
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Sustainability and Behavioral Science

Abstract: To provide practitioners with useful information about how to promote proenvironmental behavior (PEB), a meta-analysis was performed on 87 published reports containing 253 experimental treatments that measured an observed, not self-reported, behavioral outcome. Most studies combined multiple treatments, and this confounding precluded definitive conclusions about which individual treatments are most effective. Treatments that included cognitive dissonance, goal setting, social modeling, and prompts provided the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
228
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 602 publications
(240 citation statements)
references
References 150 publications
6
228
2
4
Order By: Relevance
“…Several meta-analyses (e.g. Bamberg and M€ oser, 2007;Osbaldiston and Schott, 2012) have shown that sociodemographic variables, such as gender, age and education level, have an effect on ERB. The meta-analyses indicate that nearly all psychological states have been put forward at some point as antecedents of, or motives for, ERB.…”
Section: The Importance Of Recycling In Communitiesmentioning
confidence: 99%
“…Several meta-analyses (e.g. Bamberg and M€ oser, 2007;Osbaldiston and Schott, 2012) have shown that sociodemographic variables, such as gender, age and education level, have an effect on ERB. The meta-analyses indicate that nearly all psychological states have been put forward at some point as antecedents of, or motives for, ERB.…”
Section: The Importance Of Recycling In Communitiesmentioning
confidence: 99%
“…Much of the literature on energy demand management in the home and workplace focuses on how to alter occupant behaviour, given the large variation this causes in building energy use, even between identical buildings and spaces. Behaviour change interventions have adopted multiple strategies to encourage energy-saving behaviours including education, persuasion, incentivisation, role models, physical restructuring of environments and deeper 'enabling' forms of engagement (Kollmus and Agyeman 2002;Osbaldiston and Schott 2012;Lo et al 2012). A persistently popular approach is the provision of energy feedback, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of research aimed at increasing individuals' performance of environmentally sustainable behaviors has generally taken one of two approaches (for reviews of workplace interventions see Osbaldiston & Schott, 2012;Unsworth, 2015;Young et al, in press). First, studies based on psychological theories such as Theory of Planned Behavior (e.g., Fielding, McDonald, & Louis, 2008), the Values-Beliefs-Norms model (e.g., Stern, 2000), Self-Determination Theory (e.g., Pelletier, Tuson, Green Demers, Noels, & Beaton, 1998), or a normative or leadership approach (e.g., Andersson et al, 2005;Cialdini, 2003;Graves, Sarkis, & Zhu, 2013;Kim, Kim, Han, Jackson, & Ployhart, 2014;Walls & Hoffman, 2013) have aimed to motivate people by influencing their environmental and altruistic values, perceived social and personal norms related to environmentally sustainable behaviors, knowledge of climate change, and attitudes towards the environment and climate change (e.g., Bamberg & Moser, 2007;Black, Stern, & Elworth, 1985;Dono, Webb, & Richardson, 2010;Fielding, Terry, Masser, & Hogg, 2008;Han, Nieuwenhijsen, de Vries, Blokhuis, & Schaefer, 2013;Stern, Dietz, & Guagnano, 1995;Sussman, Greeno, Gifford, & Scannell, 2013).…”
mentioning
confidence: 99%
“…In sum, these two approaches have provided mixed effects at best (see Osbaldiston & Schott, 2012;Young et al, in press). …”
mentioning
confidence: 99%